Optimizing the Legal Framework of Digital Population Identity Within the Legal System and Public Service Delivery: an Empirical Study in Aceh Besar Regency - Maulya Ulfah; Husni Husni; Iman Jauhari (International Journal of Law, Crime and Justice, 2026)
Digital Population Identity (DPI) is a digital transformation policy in the field of civil registration aimed at enhancing the effectiveness and efficiency of public service delivery. However, its implementation in Aceh Besar Regency continues to face a range of challenges, limiting its optimal utilization. This study examines the legal framework governing DPI, identifies the obstacles encountered in its implementation, and formulates strategies for strengthening its legal regulation within the public service system of Aceh Besar Regency. The research employs an empirical legal method with a socio-legal approach. Data were collected through interviews with relevant stakeholders and supported by a literature review of statutory regulations, books, academic journals, and other relevant legal sources. The findings indicate that the legal framework for DPI, as regulated under Minister of Home Affairs Regulation Number 72 of 2022, has not yet provided sufficient legal certainty, particularly because it does not explicitly require public service institutions to recognize and accept DPI. Its implementation is further constrained by limited financial and institutional capacity, inadequacies within the regulatory framework, and low public acceptance, all of which contribute to the low rate of DPI activation in Aceh Besar Regency. To address these challenges, the study recommends strengthening local regulations, harmonizing personal data protection policies, enhancing institutional capacity, expanding public outreach programs, and reinforcing oversight mechanisms to support the development of an effective, accountable, and inclusive digital public service system.